The Model of Learning Design based on Islamic Multicultural Education to Prevent Conflicts of Behavior - Zaitun Syahbudin; Muhammad Hanafi (Jurnal Pendidikan Islam, 2017)
This paper presents the form of multicultural conflict at SMA (Sekolah Menengah Atas/Senior High School) Kartini Regency of Rokan Hilir Riau, the supporting and inhibiting factors in application of the multicultural curriculum and design of learning model for multicultural-based PAI (Pendidikan Agama Islam /Islamic Education) to put down the conflicts among students. The research was a research and development (R&D) with qualitative approach. Research and development were conducted up to hypothetical phase. The research subjects were the teachers of PAI, Chemistry, and PKN (Pendidikan Kewarganegaraan/Civic Education). Each of subject teacher was one person, and the number of participating students were 34 people. Data collection technique was conducted by observation, interview, questionnaire, and documentation. Qualitative data processing encompassesed data collection, reduction, presentation, and verification. Based on the research results, there were conflicts at SMA Kartini caused by individual differences, interest differences, cultural and social changes. The supporting factor in application of multicultural curriculum was that all stakeholders at SMA Kartini still have tolerant attitude which can be developed and directed and the teachers at SMA Kartini have inclusive attitude. Meanwhile, the inhibiting factors in application of multicultural curriculum at SMA Kartini were the minimum facilities and infrastructure, lack of information services, and lack of supervision towards students.